Katastrofa wsteczna - Czapliński, Przemysław (Poznańskie Studia Polonistyczne. Seria Literacka, 2015)
The principal notion of the article–a “backward catastrophe”– stands for a catastrophe which occurs unseen until it becomes recognized and which broadens its destructive activity until it has been recognized. This concept in the article has been referred to the Shoah. The main thesis is that the recognition of the actual influence of the Holocaust began in Polish culture in the mid-1980s (largely it started with the film by Claude Lanzmann Shoah and the essay by Jan Błoński Biedni Polacy patrzą na getto [“The Poor Poles Look at the Ghetto”]), that is when the question: “What happened to the Jews”, assumes the form: “Did the things that happened to the Jews, also happened to the Poles?”. Cognitive and ethical reorientation leads to the revealing of the hidden consequences of the Holocaust reaching as far as the present day and undermining the foundations of collective identity. In order to understand this situation (and adopt potentially preventive actions) Polish society should be recognized as a postcatastrophic one.